Optimasi Travelling Salesman Problem Pada Angkutan Sekolah Dengan Menggunakan Algoritme Hybrid Discrete Particle Swarm Optimization (Studi Kasus: MI Salafiyah Kasim Blitar) - Ana Holifatun Nisa; Imam Cholissodin; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The policy of using school buses as a means of transportation to take students from school to home is very helpful for their role as parents. Moreover the distance between home and school is quite far and the age of students is still young. The constraints of the system between school transport can not be separated from the name of the efficiency of the time needed, but also the comfort of the students and the trust of the parents. With the optimization of the problems of the delivery route from this school bus, it is expected to minimize problems that can occur, including: traffic accidents due to the use of private vehicles; reduce fears of parents; so that it can increase student satisfaction with the optimization of delivery time. The algorithm used to optimize the Traveling Salesman Problem (TSP) problem is Hybrid Discrete Particle Swarm Optimization (HDPSO). In this study using data from students of Blitar's Salafiyah MI MI, which in the process of going to the house were divided into 2 groups, namely: the first group of 20 people and the second group of 24 people. From the results of testing the system compared to the actual data, the biggest difference was obtained on the second day of 2,69 Km (10,7%) in the first cluster and 22,8 (41%) Km in the second cluster.